Assessing the Frequency and Risk Factors Associated with Gastroesophageal Reflux Disease (GERD) in Southern Punjab, Pakistan - Rasool MF; Sarwar R; Arshad MS; Imran I; Saeed H; Majeed A; Akbar M; Chaudhry MO; Rehman AU; Ashraf W; Ahmad T; Badoghaish W; et al. (Dove Medical Press, 2021)
Muhammad Fawad Rasool,1 Rimsha Sarwar,1 Muhammad Subhan Arshad,1,2 Imran Imran,3 Hamid Saeed,4 Abdul Majeed,1 Muqarrab Akbar,5 Muhammad Omer Chaudhry,6 Anees ur Rehman,1 Waseem Ashraf,3 Tanveer Ahmad,7 Waleed Badoghaish,8 Faleh Alqahtani9 1Department of Pharmacy Practice, Faculty of Pharmacy, Bahauddin Zakariya University, Multan, 60800, Pakistan; 2Department of Pharmacy, Southern Punjab Institute of Health Sciences, Multan, 60000, Pakistan; 3Department of Pharmacology, Faculty of Pharmacy, Bahauddin Zakariya University, Multan, 60800, Pakistan; 4University College of Pharmacy, Allama Iqbal Campus, University of the Punjab, Lahore, 54000, Pakistan; 5Department of Political Science, Bahauddin Zakariya University, Multan, 60800, Pakistan; 6School of Economics, Bahauddin Zakariya University, Multan, 60800, Pakistan; 7Institute for Advanced Biosciences (Iab), CNRS UMR5309, INSERM U1209, Grenoble Alpes University, La Tronche, 38700, France; 8Department of Internal Medicine, College of Medicine, University of Tabuk, Tabuk, 71411, Saudi Arabia; 9Department of Pharmacology and Toxicology, College of Pharmacy, King Saud University, Riyadh, 11451, Saudi ArabiaCorrespondence: Muhammad Fawad Rasool; Faleh Alqahtani Email fawadrasool@bzu.edu.pk; afaleh@ksu.edu.saPurpose: Gastroesophageal reflux disease (GERD) is a highly prevalent gastrointestinal disorder with modifiable risk factors and it is associated with considerable health and economic burden. The current study was conducted to assess the frequency and risk factors related to GERD in the previously unstudied population of Southern Punjab, Pakistan.Methods: A cross-sectional study was conducted for assessing the frequency and risk factors of GERD by using a self-administered questionnaire. The gastroesophageal reflux disease questionnaire (GerdQ) was utilized to detect the presence of the disease.Results: The study included 308 participants; among them, 55.2% were female and 44.8% were male. The participants diagnosed with GERD (GerdQ score ≥ 8) were 26.6%. The various risk factors like higher BMI, past disease and smoking history, frequent use of NSAIDs, soft drinks, pickles, and spicy foods were significantly associated with GERD.Conclusion: The present study showed that GERD is prevalent in Southern Punjab and is associated with various modifiable risk factors. The ascendance of GERD can be prevented by public health education and awareness campaigns.Keywords: gastroesophageal reflux, GERD, risk factors, Southern Punjab